(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article examines the social, cultural, and individual factors influencing the development of students’ personal and creative competence based on international experience. It explores the concepts of creativity and competence, as well as their role in higher education. The importance of the educational environment and pedagogical support in fostering students’ creative potential is emphasized.